Extensive necrotizing sialometaplasia mimicking squamous cell carcinoma - Iamamoto, Bianca Miyuki; Barros, Julia Silva de; Ito, Fabio Augusto; Pires, Willian Ricardo; Junior, Ademar Takahama (Journal of Oral Diagnosis, 2025)
Necrotizing sialometaplasia is a benign, self-limiting inflammatory condition that predominantly affects the minor salivary glands, particularly in the hard palate region. It typically begins as a painless submucosal swelling that progresses into a well-defined necrotic ulcer. Due to its clinical and histopathological resemblance to malignant neoplasms, presents a significant diagnostic challenge, highlighting the importance of a thorough differential diagnosis to rule out malignancy. This article reports the case of a 64-year-old male patient with a necrotic ulcer on the hard palate, which developed progressively over the course of one month. Two incisional biopsies were performed: the first was inconclusive, while the second confirmed the diagnosis of necrotizing sialometaplasia through histopathological analysis. Although the exact etiology remains unclear, it is believed to result from localized vascular ischemia leading to glandular necrosis. It is therefore essential that dental surgeons are familiar with the differential diagnoses in order to adopt the most conservative treatment approach and avoid unnecessary or iatrogenic procedures.